THE ROLE OF THE TEACHER IN GROWING THE TALENT OF STUDENTS' INTEREST IN 1 KOTA SIGLI STATE ELEMENTARY SCHOOL - Handayani; Siti Mayang Sari; Akmaluddin; Sariakin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The role of the teacher is basically the main part of the teacher's task in carrying out his duties both related to schools and students. This is because students do not know how to develop their interests and talents. This study aims to determine the teacher's role and the teacher's efforts in developing students' interest talents at SDN 1 Kota Sigli and to find out the obstacles faced by teachers in developing students' interest talents. The research method uses a qualitative approach and a descriptive research type. Collecting data by observation, interviews, and documentation. The research subjects were school principals, teachers, homeroom teachers, students. The results of the study show that: the role of the teacher in developing the interests and talents of students at SDN 1 Kota Sigli can be seen in several aspects, namely the role of the teacher as an educator as a tutor and evaluator. Efforts made by the teacher, namely preparing various learning equipment and providing encouragement to parents of students to continue to foster and provide support to their children when they are outside the school environment. The obstacles faced by teachers in developing students' talents and interests are still the lack of desire and motivation of students in participating in learning. Another obstacle that is often experienced by teachers is the lack of support from parents for their children's progress.